2008
DOI: 10.1016/j.neuroscience.2008.05.024
|View full text |Cite
|
Sign up to set email alerts
|

Trafficking of tachykinin neurokinin 3 receptor to nuclei of neurons in the paraventricular nucleus of the hypothalamus following osmotic challenge

Abstract: Tachykinin NK3 receptor (NK3R) is a g-protein coupled receptor that is heavily expressed by magnocellular neurons of the paraventricular nucleus of the hypothalamus (PVN). Osmotic challenge is reported to activate NK3R expressed by magnocellular neurons and cause the NK3R to be internalized to the cytoplasm and perhaps the cell nucleus. In this study we show using immunoelectron microscopy that isolated nuclei from neurons in the PVN of osmotic challenged animals show a robust labeling for the NK3R. NK3R immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
36
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(46 citation statements)
references
References 52 publications
10
36
0
Order By: Relevance
“…This is consistent with previous studies showing no or weak nuclear NK 3 R labeling in PVN neurons of normal animals (Jensen et al, 2008;Misono and Lessard, 2012). In contrast, our results showed that an acute restraint stress session increased the nuclear NK 3 R density in AVP neurons of the PVN.…”
Section: 2supporting
confidence: 93%
See 2 more Smart Citations
“…This is consistent with previous studies showing no or weak nuclear NK 3 R labeling in PVN neurons of normal animals (Jensen et al, 2008;Misono and Lessard, 2012). In contrast, our results showed that an acute restraint stress session increased the nuclear NK 3 R density in AVP neurons of the PVN.…”
Section: 2supporting
confidence: 93%
“…The internalized receptor is then recycled back to the membrane or degraded in the cytoplasm by endopeptidases (Regoli et al, 1994;Khawaja and Rogers, 1996). Moreover, our group and others have located NK 3 Rs in the neuronal nuclei in the rat PVN following physiological challenges and in the ventral tegmental area (VTA) of normal rats (Howe et al, 2004;Jensen et al, 2008;Lessard et al, 2009). NK 3 Rs now belong to a sub-group of nuclear GPCRs, along with the apelin, angiotensin AT1 and bradykinin B2 receptors but not the neurokinin-1 or neurokinin-2 receptor (Lee et al, 2004;Gobeil et al, 2006).…”
Section: 2mentioning
confidence: 95%
See 1 more Smart Citation
“…NK3-R and NK1-R appear as dimers, which has been observed previously. 51,52 We also confirmed that copper up to 50 μM had a negligible effect on astrocyte viability ( Figure S4, Supporting Information).…”
Section: ■ Resultssupporting
confidence: 67%
“…Other neurotransmitter systems carry particular information, such as osmolarity or blood volume, and alter magnocellular neuron function under specific physiological conditions; however, NK3R appears to have a broad or general role in VP and OT release. The NK3R is a unique receptor on these neurons, as it translocates to the nucleus following activation by specific receptor agonists and physiological challenges (19,29,30). To date, no other G protein-coupled receptor has been shown to translocate to the nucleus of cells in vivo.…”
Section: Perspectives and Significancementioning
confidence: 99%